A ticket to ride: The unintended consequences of school transport subsidies. (April 2018) - Masi, Barbara
Highlights: This paper examines the effects of a decrease in the cost of attending further away schools among low income students. Identification is based on a policy intervention providing free transport based on distance criteria. The decrease in the cost of attending positively affects the probability of enrolling at schools outside the neighbourhood. Conversely, the decrease in cost affects negatively the quality of the school attended. Results are driven by students willing to trade quality for savings in transport costs. Abstract: This paper provides evidence of the effects of a decrease in the cost of travelling to schools outside the neighbourhood on the choice of school among low income families. I examine a policy reform that occurred in England in academic year 2007/2008, which provided free transport to low socio-economic status (SES) students to schools between 2 and 6 miles away from home only, but not to closer schools. Using confidential panel school micro data, providing information on the postcode of both schools and students' residence, I find strong evidence of a decline in the probability of attending schools closer than 2 miles. Conversely, the decrease in the cost of travelling affects negatively the quality of the school attended. Consistent with the predictions of a simple theoretical model, results suggest that the negative estimates on quality are driven by students who are willing to trade quality for savings in transport costs. This mechanism is reinforced by school over-subscription combined with distance-based admission criteria, which de facto limits choice to low quality institutions.